A vibrant data placement approach for map reduce in diverse environments - Sujatha, J; Meena, K (International Journal of Engineering and Technology, 2018)
Map reduce assumes that the computing capacity is same for each node in a cluster. Each node is assigned to the same load in homogeneous environment, hence it fully use the resources in the cluster. In such a cluster, there is likely to be various speciï¬cations of PCs or servers, which causes the abilities of the nodes to differ. If such a heterogeneous environment still uses the original Hadoop strategy that distributes data blocks into each node equally and the load is also evenly distributed to each node, then the overall performance of Hadoop may be reduced. The majorreasonis thatdifferentcomputing capacitiesbetweennodes causethetask executiontimeto differ so thatthefasterexecutionrate nodes processinglocal data blocks faster than other slower nodes do.The required data should be transferredfrom another node through the network.Becausewaitingforthedatatransmissiontimeincreasesthetask executiontime,it causestheentirejobexecution timeto becomeprolonged.